Mycoplasma bovis in North American bison (Bison bison): history, advances, and challenges - Buttke, Danielle E.; Kaplan, Bryan S.; Bragg, Tom K.; Jones, Lee C.; Malmberg, Jennifer L. (Frontiers in Ecology and Evolution, 2026)
North American bison (Bison bison) are keystone herbivores that shaped the ecology and evolution of North American prairies and peoples alike. Bison populations were pushed to near-extinction at the turn of the 20th century. Today, bison remain highly susceptible to newly introduced pathogens to which they have not evolved immunity, and Mycoplasma bovis is a significant threat to bison health. Although M. bovis is frequently associated with multifactorial bovine respiratory disease complex in its reservoir host, domestic cattle, M. bovis is a devastating primary pathogen in bison. As a fastidious, insidious, and rapidly mutating organism that lacks a cell wall, M. bovis is difficult to diagnose in an infected animal, and the lack of bison-specific knowledge and diagnostic tools further limits options for herd managers. Here we present a review of the current state of the field of M. bovis in bison, identify gaps in our understanding of bison physiology and M. bovis ecology, and we highlight the unique evolutionary differences of bison from domestic livestock. Dedicated bison research is urgently needed to improve prevention, surveillance, response, and management of M. bovis in this iconic North American wildlife species.